Solid/liquid interfacial synthesis of high conductivity polyaniline. Issue 86 (31st August 2016) - Kim, Chingu; Oh, Wangsuk; Park, Ji-Woong
Abstract : We have synthesized a high-conductivity polyaniline with few structural defects and highly ordered crystalline structures by solid/liquid interfacial polymerization. Abstract : A new method of solid/liquid interfacial polymerization of aniline in non-aqueous solutions reproducibly provides polyanilines with a higher molecular weight, lower degree of ortho -substitution, and higher degree of crystallinity, exhibiting higher electrical conductivity than the conventional aqueous method.